Automotive Sector, Assembly Plants and Productive Articulation in Cd-Juarez, Chihuahua, Mexico - El Paso, Texas, U.S.A., Business Intervention Consequences and Challenges (Global Journal of Management and Business Research, 2019)
Abstract not found
Keywords: automotive sector assembly plants productive articulation enterprises intervention